Sports sponsorship as a means of internationalisation : Creating business opportunities within networks - Neziri, Rami (My University, 2020)
The objective of this study was to examine the effect sponsorship networks have on the internationalisation process of B2B companies by utilising the ARA model. The chosen research method was a multiple case study, and the research data was gathered by conducting semi-structured interviews with representatives of each case company. The case companies were Finnish companies operating in various B2B industries and each company had some form of international presence prior to this study. The results show that sponsorship networks facilitate the internationalisation of B2B companies in many ways. Relationships with different actors resulted in the actors learning about each other and themselves resulting in an improved understanding of international business opportunities. The exchange of various types of knowledge concerning, for example, market-specific knowledge, technological knowledge, or knowledge about customers, was also a crucial component in these relationships and enabled the companies to explore and exploit opportunities. This knowledge also resulted in the companies adapting their activities to facilitate better exploitation of international business opportunities. The networks also increased the credibility of the case companies, which acted as an important facilitator of new international opportunities. Furthermore, the credibility was sometimes the result of other actors associating certain aspects of the sports organisation to the case companies. Through the networks, the case companies were also able to develop entirely unique resources which led to them being a preferred partner to other international actors within the network. This study contributed to the existing theory by expanding the network approach to sponsorship into the context of internationalisation, and many findings from earlier empirical research were supported. In addition, many managerial contributions were formulated from the viewpoint of the company and the sports organisation. Companies should seek to leverage the network by accessing important resources and developing their own activities, while sports organisations should utilise the range of their network as a selling point while also developing it. Further research should seek to examine the internationalisation of a single company more closely to enable the evaluation of this study’s findings as a part of a complete internationalisation process. In addition, future research should also aim to test the findings and theories using quantitative methods.

Tämän tutkimuksen tavoite oli tarkastella sponsoriverkostojen vaikutusta B2B-yritysten kansainvälistymiseen hyödyntäen ARA-mallia. Tutkimus toteutettiin hyödyntäen useaa tapaustutkimusta, ja tutkimusaineisto kerättiin suorittamalla teemahaastattelu jokaisen tutkimuksen kohteena olleen yrityksen edustajan kanssa. Tutkimuksen kohteena oli kolme suomalaista yritystä eri aloilta, ja jokaisella yrityksellä oli jonkinlaisia kansainvälisiä toimintoja jo ennestään. Tutkimuksen tulokset osoittavat, että sponsoriverkostot voivat edesauttaa B2B-yritysten kansainvälistymstä monin eri tavoin. Verkoston toimijat oppivat kriittisiä asioita itsestään ja muista toimijoista solmimiensa suhteiden ansiosta, mikä johti parempaan käsitykseen kansainvälisistä liiketoimintamahdollisuuksista. Erilaisen tiedon vaihto toimijoiden kesken oli myös keskeinen osa näissä suhteissa ja ne auttoivat yrityksiä tunnistamaan ja hyödyntämään kansainvälisiä mahdollisuuksia. Tämä tieto edesauttoi myös yritysten toiminnan kehittämistä, mikä mahdollisti liiketoimintamahdollisuuksien paremman hyödyntämisen. Verkostossa toimiminen kasvatti myös yritysten uskottavuutta, mikä omalta osaltaan edesauttoi kansainvälisten liiketoimintamahdollisuuksien syntymistä. Tämä uskottavuus saattoi pohjautua urheiluorganisaation piirteisiin, joita muut toimijat assosioivat myös yritykseen pelkästään toimijoiden välisen suhteen takia. Tutkimuksen yritykset pystyivät myös kehittämään harvinaisia resursseja toimimalla verkostossa, mikä teki heistä houkuttelevan yhteistyökumppanin muille verkoston toimijoille. Tämä tutkimus edisti nykyistä sponsoroinnin verkostoteoriaa käsittelemällä aihetta kansainvälistymisen näkökulmasta. Tutkimuksen tulokset tukivat suurilta osin useita sponsoroinnin ja kansainvälistymisen aikaisempia empiirisiä tutkimuksia. Lisäksi tutkimus johti useisiin käytännön toimenpide-ehdotuksiin. Yritysten tulisi hyödyntää verkostojen tarjoamia resursseja ja kehitysmahdollisuuksia, kun taas urheiluorganisaatioiden tulisi käyttää verkostotoimintaa myynnin välineenä samalla pyrkien kehittämään sitä. Jatkotutkimusten tulisi tarkastella kansainvälistymistä tarkemmin yhden yrityksen näkökulmasta, jotta tämän tutkimuksen johtopäätöksiä voidaan analysoida tarkemmin osana kokonaista kansainvälistymisprosessia. Jatkotutkimuksen tulisi myös pyrkiä testaamaan näitä johtopäätöksiä ja tässä tutkimuksessa esiteltyjä teorioita käyttäen kvantitatiivisia menetelmiä.
Keywords: sponsorship, networks, internationalisation, ARA model